Biological Control of Insect Pests by Bacterial Species Present in the Environment - Azize, Eman Mohamed Taher; Mohammed, Dalia Abdulelah; Yaseen, Aulfat TahseIn (Journal of agricultural, environmental and veterinary sciences, 2021)
Because of the severe damage caused by insect pests in agricultural fields, which cost billions of dollars annually, countries used chemical pesticides to eliminate these pests. The continuous use of chemical pesticides led to many environmental impacts, besides the emergence of resistance to insect pests. Therefore, it was necessary to search for an effective treatment for insect pest problems that was environmentally friendly and safe for human health. Biological control of insect pests has gained considerable importance in agricultural fields for its efficiency and safety for humans and other non- target organisms. In addition to its natural presence in the environment, cheaper cost, and more environmentally friendly, And a better alternative to synthetic chemical pesticides as well as being environmentally safe, they not only help establish food security by fighting against insect pests but also ensure food safety, they have enormous potential for achieving agricultural sustainability and environmental safety. In this review, we will highlight the definition and classification of insect pests, microbial pesticides. Besides, the advantages and disadvantages of these kinds of pesticides. We will also focus on the most effective bacterial species used in the production of pesticides and protein toxins that kill insect pests, their mechanism of action, method of marketing, and application to insect pests. We have looked at future research in eradicating insect pests.